Roux-en-Y gastric bypass and sleeve gastrectomy induce substantial and persistent changes in microbial communities and metabolic pathways - Jerry T. Dang; Valentin Mocanu; Heekuk Park; Michael Laffin; Naomi Hotte; Shahzeer Karmali; Daniel W. Birch; Karen L. Madsen (Gut Microbes)
Bariatric surgery induces significant microbial and metabolomic changes, however, links between microbial and metabolic pathways have not been fully elucidated. The objective of this study was to conduct a comprehensive investigation of the microbial, metabolomic, and inflammatory changes that occur following Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG). A prospective clinical trial was conducted with participants undergoing RYGB, SG, and non-operative controls (CTRL). Clinical parameters, blood samples, and fecal samples were collected pre-intervention and at 3 and 9 months. A multi-omics approach was used to perform integrated microbial-metabolomic analysis to identify functional pathways in which weight loss and metabolic changes occur after surgery. RYGB led to profound microbial changes over time that included reductions in alpha-diversity, increased Proteobacteria and Verrucomicrobiota, decreased Firmicutes, and numerous changes at the genera level. These changes were associated with a reduction in inflammation and significant weight loss. A reduction in Romboutsia genera correlated strongly with weight loss and integrated microbial-metabolomic analysis revealed the importance of Romboutsia. Its obliteration correlated with improved weight loss and insulin resistance, possibly through decreases in glycerophospholipids. In contrast, SG was associated with no changes in alpha-diversity, and only a small number of changes in microbial genera. A cluster of Firmicutes genera including Butyriciccocus, Eubacterium ventriosum, and Monoglobus was decreased, which correlated with decreased weight, insulin resistance, and systemic inflammation. This work represents comprehensive analyses of microbial-metabolomic changes that occur following bariatric surgery and identifies several pathways that are associated with beneficial metabolic effects of surgery.